Fintech renaissance: powering efficiency in Asian banking through country competitiveness - Chowdhury, Mozaffar Alam; Ni, Soh Wei; Abdul Rahim, Norhuda; Johari, Jalila (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of the study is to examine Fintech innovations that boost bank efficiency while controlling for country competitiveness in Asia. The study employs cross-country data from a sample of 92 commercial banks in Asia and uses data envelopment analysis (DEA) to analyze the efficiency of banks from 2016 to 2022. The panel data regression utilized a fixed-effect model, which was run after a diagnostic check. The validated data satisfied the criteria for stationary, serial autocorrelation, heteroscedasticity, homogeneity, and multicollinearity. The findings show that Fintech significantly improves bank efficiency with the mediating effect of country competitiveness. Additionally, the results indicate that Fintech has a positive correlation with bank efficiency in developing countries. In developed countries, the correlation between Fintech and bank efficiency is also positive. In developing countries, the Fintech effect is greater when country competitiveness is considered, and the effect is much more pronounced in terms of magnitude due to competitiveness. The study contributes to the literature on the relationships between Fintech and bank efficiency by using country competitiveness as a mediating factor. The implication is derived from the empirical evidence that country competitiveness provides a supportive environment for enhancing efficiency in Asian banks.